Open Science and its role in global scientific collaboration - Garcés-Giraldo, Luis Fernando; García-Arango, David Alberto; Ohcoa, José Alexander Velásquez; Zuluaga, Conrado Giraldo; Rodríguez-Flores, Eduar Antonio; Suárez-Pizzarello, Marianella; Montoya-Guiral, Leonardo Fabio (Journal of Posthumanism, 2025)
Open Science has transformed the generation and dissemination of scientific knowledge, promoting transparency and accessibility, the present study evaluates the impact of Open Science on the reproducibility and transparency of research through a mixed-methods approach, the methodology includes a bibliometric analysis using the Bibliometrix software, where 536 articles on Open Science extracted from Scopus were analyzed, Of these, 30 studies were selected with specific inclusion criteria such as: methodological rigor, empirical and theoretical relevance in the topics of transparency and scientific production. Likewise, a systematic review was carried out according to the PRISMA protocol to identify challenges and opportunities of Open Science in diverse areas, such as space exploration, health research and criminology.